2013
DOI: 10.1590/s1413-78522013000600001
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos in vitro da cafeína na cartilagem de crescimento de ratos

Abstract: Objective To evaluate the in vitro effetcs of caffeine on proliferation, apoptosis a nd gene transcripts expression of chondrogenic differentiation in growth cartilage. Methods The cartilaginous epiphyses of femurs of newborn rats, which were divided into two subgroups: treated with caffeine and control group, both observed over the time periods of 0, 7, 14 and 21 days. The cartilaginous epiphyses of femurs of each subgroup and each time span were subjected to histomorphometric, immunohistochemical analysis, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…65 In addition, caffeine has been associated with increased apoptosis, chondrocyte phenotype alterations, and ECM perturbations in offspring exposed in utero. [66][67][68][69] As such, these factors and pathways deserve further attention for elucidating caffeinerelated disease mechanisms for IVD degeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…65 In addition, caffeine has been associated with increased apoptosis, chondrocyte phenotype alterations, and ECM perturbations in offspring exposed in utero. [66][67][68][69] As such, these factors and pathways deserve further attention for elucidating caffeinerelated disease mechanisms for IVD degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…However, changes reflective of those observed in degenerative IVDs (ie, cell death, loss of ECM integrity and architecture, decreased disc height, water content, PG content, and increased stiffness) have been successfully reproduced using needle puncture to simulate disc injury. 2,[65][66][67][68][69]72 RWV bioreactors recreate the physiologic microgravity environment inducing sheer stresses on cultured tissues, generating laminar fluid-flow that reduces diffusional limitations, producing more efficient nutrient-waste exchange. 7,[73][74][75][76] Furthermore, this flow serves as a cell signaling and communication pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Caffeine (1,3,7-trimethylxanthine) is a natural alkaloid belonging to the family of methylxantines [23][24][25][26][27][28][29][30][31]. The main caffeine sources are tea leaves, cola nuts, and coffee and cocoa beans [23][24][25][26][27][28][29][30][31][32].…”
Section: Caffeinementioning
confidence: 99%
“…Nonetheless, it is among the most frequently consumed substances, with an average daily ingestion of 120 mg [23][24][25][26][27][28][29][30][31][32]. It is present in beverages (e.g., coffee, tea, soft drinks, and energy drinks), food (e.g., cocoa and chocolate) [23][24][25][26][27][28][29][30][31][32], and some stimulants and is used as an adjuvant to increase the absorption of some medications [23][24][25][26][27][28][29][30][31]. Studies show that coffee (60%-75%) and tea (15%-30%) are the main sources of caffeine for adults, while among children, chocolate and soft drinks are the major intake sources [30][31][32] (Figure 3).…”
Section: Caffeinementioning
confidence: 99%
“…For example, current studies in humans have shown that the birth defects induced by maternal caffeine intake include low birth weight, childhood overweight, and cognitive impairment (Qian et al, 2019 ). The caffeine exposure has been also reported to disrupt chondrogenesis and osteogenesis (Wink et al, 1996 ; Reis et al, 2013 ). As far as we know, muscle and cartilage cells are derived from the somites during the early stage of embryonic development (Christ and Ordahl, 1995 ; Jang and Baik, 2013 ).…”
Section: Introductionmentioning
confidence: 99%